2002
DOI: 10.1177/0886368702034002007
|View full text |Cite
|
Sign up to set email alerts
|

Plan Design and Work/ Life Management in Incentive Compensation

Abstract: or many organizations during the bull market of the 1990s, attracting, retaining and motivating highly qualified employees was a matter of offering them sufficiently large stock grants, option grants and/or bonuses. Often despite their profitability, growth in the market capitalization of these organizations ensured a growth in the market value of their stock and, at the same time, ensured employees that their options would remain "in the money." So long as profitability was not a major concern, it was also re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…For example, a 2002 survey conducted by the National Opinion Research Center of the University of Chicago indicated that among public companies with 500 or more employees, only 23% percent use broad-based stock option plans (defined as a plan in which at least 50% of employees are eligible to receive stock options). stock options are a source of financing (Yermack, 1995;Guay, 1999, 2001) and an important part of a comprehensive human resource management program (Blasi et al, 1996(Blasi et al, , 2003Liccione, 2002;Lam and Ho, 2006). I therefore predict that the more cash constrained are private venture-backed firms, the more likely they are to grant options deeply to their employees in order to conserve cash.…”
Section: Stock Options As a Source Of Financingmentioning
confidence: 97%
“…For example, a 2002 survey conducted by the National Opinion Research Center of the University of Chicago indicated that among public companies with 500 or more employees, only 23% percent use broad-based stock option plans (defined as a plan in which at least 50% of employees are eligible to receive stock options). stock options are a source of financing (Yermack, 1995;Guay, 1999, 2001) and an important part of a comprehensive human resource management program (Blasi et al, 1996(Blasi et al, , 2003Liccione, 2002;Lam and Ho, 2006). I therefore predict that the more cash constrained are private venture-backed firms, the more likely they are to grant options deeply to their employees in order to conserve cash.…”
Section: Stock Options As a Source Of Financingmentioning
confidence: 97%
“…Since granting employee stock options involves no outlay of cash by the firm, the more its employees' total compensation is tilted toward stock options, the less are the cash demands put on the firm. Thus, all else held equal, stock options are a source of financing (Yermack, 1995;Guay, 1999, 2001) and an important part of a comprehensive human resource management program (Blasi et al, 1996(Blasi et al, , 2003Liccione, 2002;Lam and Ho, 2006).…”
Section: Stock Options As a Source Of Financingmentioning
confidence: 99%